P16/Ki-67 Immunostaining is Useful in Stratification of Atypical Metaplastic Epithelium of the Cervix - Ann E. Walts M.D; Shikha Bose (SAGE Publishing, 2008)
Cervical metaplastic squamous epithelium exhibiting atypia insufficient for a diagnosis of cervical intraepithelial neoplasia (CIN) is usually reported as "atypical squamous metaplasia" (ASM). Stratification impacts treatment since the differential is often between reactive and high grade CIN (CIN II, III). Diagnosis with H&E is associated with low intra/interobserver concurrence. P16/Ki-67 immunostains are helpful to assess cervical biopsies for HPV-associated lesions but staining in metaplastic squamous epithelium has received little attention. This study aims to establish staining characteristics of metaplastic squamous epithelium and determine if p16/Ki-67 is useful in ASM stratification. 80 cervical biopsies containing morphologically normal and dysplastic squamous metaplasia were retrieved to determine the staining characteristics of metaplastic epithelium utilizing p16/Ki-67 immunostains. These included 21 benign squamous metaplasia (BSM) from benign cervices, 15 BSM present adjacent to HPV/CIN lesions, and 44 CIN involving squamous metaplasia. Serial sections with controls were stained for p16 and Ki-67 and in-situ hybridization (ISH) for low-risk (LR) and high-risk (HR) HPV was performed. P16 was recorded as negative, spotty, or band-like. Ki-67 was recorded as positive when present in >50% of lesional nuclei. Results were correlated with H&E diagnosis. 95% of the BSMs, whether from normal cervices or adjacent to HPV/CIN were p16/Ki-67 negative. 81% HG CINs involving squamous metaplasia were p16 band/Ki-67 positive. Low grade CIN (CIN I) involving metaplastic epithelium showed a broad distribution of p16/Ki-67 staining patterns. Based on these criteria, 20 ASM were evaluated. 10% of the ASM cases were p16 band/Ki-67 positive indicating HG CIN. 60% of the ASMs were p16/Ki-67 negative indicating reactive change (all with the exception of one case being HPV negative). The remaining 30% of the ASM cases showed variable positivity for p16 and Ki-67 and could not be stratified into the two categories. Thus p16/Ki-67 staining is helpful in stratification of ASM as reactive or CIN.